Applicability of avidin protein coated mesoporous silica nanoparticles as drug carriers in the lung. Issue 15 (29th March 2016) - van Rijt, S. H.; Bölükbas, D. A.; Argyo, C.; Wipplinger, K.; Naureen, M.; Datz, S.; Eickelberg, O.; Meiners, S.; Bein, T.; Schmid, O.; Stoeger, T.
Abstract : We demonstrate that avidin-coated mesoporous silica nanoparticles (MSN-AVI) offer potential for lung application. We show that surface modifications can greatly affect toxicity and cell type specific uptake, highlighting the importance of these types of studies for future development of nanomedicines. Abstract : Mesoporous silica nanoparticles (MSNs) exhibit unique drug delivery properties and are thus considered as promising candidates for next generation nano-medicines. In particular, inhalation into the lungs represents a direct, non-invasive delivery route for treating lung disease. To assess MSN biocompatibility in the lung, we investigated the bioresponse of avidin-coated MSNs (MSN-AVI), as well as aminated (uncoated) MSNs, after direct application into the lungs of mice. We quantified MSN distribution, clearance rate, cell-specific uptake, and inflammatory responses to MSNs within one week after instillation. We show that amine-functionalized (MSN-NH2 ) particles are not taken up by lung epithelial cells, but induced a prolonged inflammatory response in the lung and macrophage cell death. In contrast, MSN-AVI co-localized with alveolar epithelial type 1 and type 2 cells in the lung in the absence of sustained inflammatory responses or cell death, and showed preferential epithelial cell uptake in in vitro co-cultures. Further, MSN-AVI particles demonstrated uniform particle distribution in mouse lungs and slow clearance rates. Thus, we provide evidence that avidin functionalized MSNs (MSN-AVI) have the potential to serve as versatile biocompatible drug carriers for lung-specific drug delivery.